1996
DOI: 10.3109/01050399609047999
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Conditioning Click on Click-evoked Otoacoustic Emission

Abstract: The effects of the preceding (conditioning) click on the evoked otoacoustic emission (EOAE) to the following (test) click were investigated in normally hearing adults. To overcome distortions due to superimposition of the test EOAE on the EOAE to the conditioning click, a special stimulation and response subtraction procedure was utilized. The conditioning stimulus was found to suppress the test EOAE. The suppression lessened with a decrease in the conditioning stimulus level and an increase in the time interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 14 publications
2
6
0
Order By: Relevance
“…3) is quantitatively comparable to the suppression reported by Hine and Thornton (2002), who found maximal suppression of 4-5 dB at an ICI of 1 ms for stimulus-levels of 65 dB peSPL and time-frames between 7 and 17 ms. Qualitatively, the data of Tavartkiladze et al (1994) and Kevanishvili et al (1996) showed similar trends of suppression as a function of ICI. Augmentation of the CEOAE (i.e., S < 0) was observed using method 1 for ICIs between 5 and 8 ms and for time-frames between 15 and 21 ms (upper-left panel in Fig.…”
Section: Resultssupporting
confidence: 60%
See 4 more Smart Citations
“…3) is quantitatively comparable to the suppression reported by Hine and Thornton (2002), who found maximal suppression of 4-5 dB at an ICI of 1 ms for stimulus-levels of 65 dB peSPL and time-frames between 7 and 17 ms. Qualitatively, the data of Tavartkiladze et al (1994) and Kevanishvili et al (1996) showed similar trends of suppression as a function of ICI. Augmentation of the CEOAE (i.e., S < 0) was observed using method 1 for ICIs between 5 and 8 ms and for time-frames between 15 and 21 ms (upper-left panel in Fig.…”
Section: Resultssupporting
confidence: 60%
“…This is in agreement with Tavartkiladze et al (1994), who reported augmentation of the CEOAE for an ICI of 7 ms. However, Kevanishvili et al (1996) and Hine and Thornton (2002) have not observed augmentation for the short-latency CEOAE in the double-click paradigm.…”
Section: Resultsmentioning
confidence: 71%
See 3 more Smart Citations